Centella asiatica (L.) Urb. Prevents Hypertension and Protects the Heart in Chronic Nitric Oxide Deficiency Rat Model - Bunaim, Mohd Khairulanwar; Kamisah, Yusof; Mohd Mustazil, Mohd Noor; Fadhlullah Zuhair, Japar Sidik; Juliana, Abdul Hamid; Muhammad, Norliza (Frontiers in Pharmacology, 2021)
Background: Hypertension is a major risk factor for cardiovascular disease (CVD), which is the number one cause of global mortality. The potential use of natural products to alleviate high blood pressure has been demonstrated to exert a cardioprotective effect. Centella asiatica (L,) Urb belongs to the plant family Apiaceae (Umbelliferae). It contains a high amount of triterpenoid and flavonoid that have antioxidant properties and are involved in the renin-angiotensin-aldosterone system (RAAS), which is an important hormonal system for blood pressure regulation. Objective: This study aimed to investigate the effects of C. asiatica ethanolic extract on blood pressure and heart in a hypertensive rat model, which was induced using oral N(G)-nitro-L-arginine methyl ester (L-NAME). Methods: Male Sprague-Dawley rats were divided into five groups and were given different treatments for eight weeks. Group 1 only received deionized water. Groups 2, 4, and 5 were given L-NAME (40 mg/kg, orally). Groups 4 and 5 concurrently received C. asiatica extract (500 mg/kg, orally) and captopril (5 mg/kg, orally), respectively. Group 3 only received C. asiatica extract (500 mg/kg body weight, orally). Systolic blood pressure (SBP) was measured at weeks 0, 4, and 8, while serum nitric oxide (NO) was measured at weeks 0 and 8. At necropsy, cardiac and aortic malodialdehyde (MDA) content, cardiac angiotensin-converting enzyme (ACE) activity, and serum level of brain natriuretic peptide (BNP) were measured. Results: After eight weeks, the administrations of C. asiatica extract and captopril showed significant (p < 0.05) effects on preventing the elevation of SBP, reducing the serum NO level, as well as increasing the cardiac and aortic MDA content, cardiac ACE activity, and serum BNP level. Conclusion: C. asiatica extract can prevent the development of hypertension and cardiac damage induced by L-NAME, and these effects were comparable to captopril.